Towards effective administration of Art Departments in selected Senior Secondary Schools in Kumasi - Nkansah, Joseph Oduro (2011)
A thesis presented to the school of Graduate Studies, Kwame Nkrumah University of Science and Technology, in partial fulfilment of the requirement for the Degree of Master of Arts in Art Education.